Real-time dose adjustment using point-of-care platelet reactivity testing in a double-blind study of prasugrel in children with sickle cell anaemia - Jakubowski, Joseph A.; Hoppe, Carolyn C.; Zhou, Chunmei; Smith, Brendan E.; Brown, Patricia B.; Heath, Lori E.; Inusa, Baba; Rees, David C.; Small, David S.; Gupta, Neehar; Yao, Suqin; Heeney, Matthew M.; Kanter, Julie (Thrombosis and Haemostasis, 2017)
Patients with sickle cell anaemia (SCA) have vaso-occlusive crises resulting from occlusive hypoxic-ischaemic injury. Prasugrel inhibits platelet activation and aggregation involved in SCA pathophysiology. Determining Effects of Platelet Inhibition on Vaso-Occlusive Events (DOVE) was a phase 3, double-blind, randomised, placebo-controlled trial assessing prasugrel efficacy. DOVE sought to bring patients’ P2Y12 reaction unit (PRU) value within a targeted range via prasugrel dose adjustments using encrypted VerifyNow P2Y12® (VN-P2Y12) point-of-care testing and an interactive voice-response system (IVRS). After PRU determination, randomised patients received 0.08 mg/kg/day prasugrel or placebo. Encrypted PRUs and IVRS provided double-blind dose adjustments to achieve a defined PRU target range of 136–231; placebo patients had mock titrations. Of 341 randomised patients, 166 placebo and 160 prasugrel patients reached the fully titrated dose (FTD). Most prasugrel patients (n=104, 65 %) remained on the initial 0.08 mg/kg dose; doses escalations occurred in 23 % of patients (n=36). Mean PRUs for the pharmacodynamic population at baseline were similar in the prasugrel (273 ± 44.9) and placebo groups (273 ± 51.7), with significant reductions in PRU (p<0.001) for prasugrel patients at the FTD and at 9 months. Concomitant use of hydroxyurea did not affect platelet reactivity at any time. The majority of prasugrel patients (n=135, 84.4 %) at the FTD were within the target range of 136–231 PRUs. Mean VN-P2Y12 percentage inhibition at baseline was similar in the prasugrel (2.8 ± 5.4 %) and placebo groups (2.0 ± 4.7 %); prasugrel patients had significant increases in inhibition (p<0.001) at FTD and at 9 months. Patients with higher PRU values at baseline required higher prasugrel doses to bring PRU within the prespecified range. DOVE is the first study to successfully employ double-blind, real-time, encrypted, point-of-care platelet testing and IVRS to dose-adjust antiplatelet therapy to a targeted range of platelet inhibition.
Keywords: Prasugrel; VerifyNow; platelets; clinical trial; antiplatelet